Impact of diverse cultivars on molecular and crystalline structures of rice starch for food processing. (1st August 2017) - Lee, Seul; Lee, Ju Hun; Chung, Hyun-Jung
Highlights: The properties of starches in rice cultivars for major food processing. Physicochemical properties of rice starches were affected by molecular structure. Rice starch from cooked rice varieties showed higher viscosity. Rice starch from rice cake varieties had higher SDS content. Rice varieties were clearly classified according to processing adaptability. Abstract: The objective of this study was to determine the molecular and crystalline structures of starches from diverse rice cultivars for three major food processing in Korea (cooked rice, brewing and rice cake). Rice starches were isolated from 10 different rice varieties grown in Korea. Apparent amylose contents of rice starches from cooked rice, brewing and rice cake varieties were 21.1–22.4%, 22.9–24.6%, and 20.1–22.0%, respectively. Rice starches from rice cake varieties showed higher peak viscosity but lower pasting temperature than those from cooked rice and brewing varieties. Swelling factor at 80 °C of rice starches from cooked rice, brewing and rice cake varieties was 16.6–19.0, 17.8–19.3, and 17.8–19.2, respectively. Based on structure and physicochemical properties of rice starches extracted from different rice varieties, principal component analysis (PCA) results showed that these rice varieties could be clearly classified according to processing adaptability for cooked rice and rice cake.